On Behavior Laplace Integral Operators with Generalized Bessel Matrix Polynomials and Related Functions - Muajebah Hidan; Mohamed Akel; Salah Mahmoud Boulaaras; Mohamed Abdalla (Journal of Function Spaces)
Recently, the applications and importance of integral transforms (or operators) with special functions and polynomials have received more attention in various fields like fractional analysis, survival analysis, physics, statistics, and engendering. In this article, we aim to introduce a number of Laplace and inverse Laplace integral transforms of functions involving the generalized and reverse generalized Bessel matrix polynomials. In addition, the current outcomes are yielded to more outcomes in the modern theory of integral transforms.